Crossing Nuclear Thresholds Leveraging Sociocultural Insights into Nuclear Decisionmaking (Initiatives in Strategic Studies: Issues and Policies, 2018)
This book applies the cutting-edge socio-cultural model Cultural Topography Analytic Framework (CTAF) pioneered in the authors' earlier volume Strategic Culture and Weapons of Mass Destruction: Culturally Based Insights into Comparative National Security Policymaking (Palgrave Macmillan, 2009) with an eye towards isolating those vectors of nuclear decision-making on which the US might exert influence within a foreign state. The case studies included in this volume tackle a number of the nuclear challenges-termed "nuclear thresholds"-likely to be faced by the US and identify the most promising points of leverage available to American policymakers in ameliorating a wide range of over-the-horizon nuclear challenges. Because near and medium-term nuclear thresholds are likely to involve both allies and adversaries simultaneously, meaning that US response will require strategies tailored to both the perception of threat experienced by the actors in question, the value the actors place on their relationship with the US, and the domestic context driving decision-making. This volume offers a nuanced look at each actor's identity, national norms, values, and perceptual lens in order to offer culturally-focused insights into behavior and intentions. .